Characterization of Endothelial and Smooth Muscle Cells From Different Canine Vessels - Oosterhoff, Loes A.; Kruitwagen, Hedwig S.; van Wolferen, Monique E.; van Balkom, Bas W.M.; Mokry, Michal; Lansu, Nico; van den Dungen, Noortje A.M.; Penning, Louis C.; Spanjersberg, Talitha C.F.; de Graaf, Johannes W.; Veenendaal, Tomas; Zomerdijk, Flin; et al. (Frontiers in Physiology, 2019)
Vasculature performs a critical function in tissue homeostasis, supply of oxygen and nutrients, and the removal of metabolic waste products. Vascular problems are implicated in a large variety of pathologies and accurate in vitro models resembling native vasculature are of great importance. Unfortunately, existing in vitro models do not sufficiently reflect their in vivo counterpart. The complexity of vasculature requires the examination of multiple cell types including endothelial cells (ECs) and vascular smooth muscle cells (VSMCs), as well as vessel location in the body from which they originate. The use of canine blood vessels provides a way to study vasculature with similar vessel size and physiology compared to human vasculature. We report an isolation procedure that provides the possibility to isolate both the endothelial and smooth muscle cells from the same vessels simultaneously, enabling new opportunities in investigating vasculature behavior. Canine primary ECs and VSMCs were isolated from the vena cava, vena porta and aorta. All tissue sources were derived from three donors for accurate comparison and to reduce inter-animal variation. The isolation and purification of the two distinct cell types was confirmed by morphology, gene- and protein-expression and function. As both cell types can be derived from the same vessel, this approach allows accurate modeling of vascular diseases and can also be used more widely, for example, in vascular bioreactors and tissue engineering designs. Additionally, we identified several new genes that were highly expressed in canine ECs, which may become candidate genes for novel EC markers. In addition, we observed transcriptional and functional differences between arterial- and venous-derived endothelium. Further exploration of the transcriptome and physiology of arteriovenous differentiation of primary cells may have important implications for a better understanding of the fundamental behavior of the vasculature and pathogenesis of vascular disease.